An option pricing approach to optimal bidding in construction projects - Ribeiro, João A. (2018)
Reaching an optimal mark‐up value in the context of construction projects' bidding competitions has been a research topic for more than 40 years. This paper aims to contribute to this debate by applying a real options approach. The proposed model has a pure theoretical nature and is based on a maximization problem, whose outcome is the optimal price, that is, the price that should be included in the bid proposal. The model is later extended to accommodate the existence of penalty costs if the selected bidder refuses to enter into contract. Results reached using a numerical example demonstrate that the optimal price is higher when penalty costs are considered.